STRATEGI PUBLIC RELATIONS PT KILANG PERTAMINA INTERNASIONAL REFINERY UNIT IV CILACAP DALAM MEMPERKUAT PEMBERDAYAAN PASAR SEMOK (SMALL ENTERPRISE MEDIUM OF KEMIREN ASRI) DI KELURAHAN TEGALKAMULYAN KECAMATAN CILACAP SELATAN KABUPATEN CILACAP - Fajri Akhla Sabilah; Hanifah Muyasaroh (Hujjah: Jurnal Ilmiah Komunikasi dan Penyiaran Islam, 2023)
PT Kilang Pertamina International RU IV Cilacap as a global energy company, has a sustainability commitment to strengthen social development by running the PERTAMINA CSR (Corporate Social and Environmental Responsibility) program through sustainable community empowerment aimed at realizing community economic independence by establishing and fostering Micro Small Units (UMK) which is run through the UMK Funding Program so as to encourage UMK to upscale. This study aims to determine the public relations strategy of PT Kilang Pertamina International RU IV Cilacap in managing relationships with the Kemiren Asri Group, as well as strategies and factors in strengthening the empowerment of the SEMOK (Small Enterprise Medium of Kemiren Asri) Market. This research is a type of field research conducted using a qualitative approach. The presentation method used in the research is through observation, interviews, and documentation. From the research results that have been prosented, the gradual community empowerment in Kemiren Village has produced many beneficial results for the community. A unique condition and has a value chain where all activities in Kemiren Asri are related, and form a zero waste system, where no waste is wasted from all production activities of the Kemiren Asri Group. To develop Kemiren at a higher stage, the company together with the community developed the marketing of Kemirean Asri product through SEMOK Market (Small Enterprise Medium Of Kemiren Asri). In order to achieve success in every condition faced by the company, PT Kilang Pertamina International RU IV Cilacap uses four steps of public relations strategy in carrying out CSR programs, starting from the planning, implementation, monitoring, and evaluation stages. The SEMOK Market program implementations system was initiated by PT Kilang Pertamina International RU IV Cilacap and the Kemiren Asri Group from the evaluation results, and involved all stakeholders in providing access and support to encourage self-help communities.